Parallel Graft Technique in a Complex Aortic Aneurysm: The Value of Intra-operative Flexibility from The Original Operative Plan. (2019) - Castro-Ferreira, Ricardo; Dias, Paulo G.; Sampaio, Sérgio M.; Teixeira, José F.; Lobato, Armando C.
Abstract : Introduction: The parallel grafting technique (PGT) is a valuable alternative to prefabricated branched or fenestrated endovascular aortic repair. An often overlooked advantage of PGT is its unique adaptability to different anatomical challenges that might appear intra-operatively. Report: A 72 year old male patient presented with a 60 mm thoracic aneurysm, 59 mm juxtarenal abdominal aortic aneurysm, and 32 mm common iliac aneurysm (CIAA). Thoracic endovascular aortic repair plus endovascular aortic repair with bilateral renal artery chimneys and CIAA exclusion applying the sandwich technique was proposed. Because of unfavourable angulation it was not possible to achieve selective left renal catheterisation via axillary access. Changing to a femoral approach allowed successful retrograde catheterisation. The procedure ended with a chimney for the right renal artery and a periscope for the left renal artery. The final angiogram showed no endoleaks and renal and hypogastric patency. The patient was discharged three days after the procedure and remains under ultrasound surveillance after 40 months because of a small type two endoleak. Conclusion: When using a prefabricated branched device, the possibility of selectively catheterising a visceral branch often has no straightforward solution. However, parallel grafting is an extremely flexible technique, which was of paramount importance for the surgical outcome of the present case. Highlights: The parallel grafting technique (PGT) can be a valuable alternative to prefabricated branched or fenestrated endovascular aortic repair. An often overlooked advantage of PGT is its unique adaptability to different anatomical challenges that might appear intra-operatively. This is a complex case report with three year follow up, in which three consecutive aneurysms were treated with PGT. In this case the unique adaptability of the technique was paramount for the outcome of the surgery.